Harmonic distortion and voltage imbalance study of photovoltaic power plant connected to the Malaysian grid - Al-Shetwi, Ali Q.; Muhamad Zahim, Sujod (UTeM, 2018)
This paper presents power quality analysis on the effects of large-scale photovoltaic power plant (PVPP) connected to the distribution system of Malaysian grid. For this purpose, the PVPP system with a capacity of 1.5 MW is connected to the medium voltage level of the distribution network through a single-stage voltage source inverter (VSI). Power quality issues at connection point such as current and voltage harmonics distortion and voltage imbalance have been studied based on the standard requirements especially Malaysian standards at different levels of solar irradiation. This analysis is very useful to help researchers and grid operators to study the effects of power quality problems concerning gridconnected PVPP. It can be clearly seen from the measured results that the harmonic distortion and voltage imbalance of the proposed PVPP can meet the Malaysian distribution grid code and national grid standard requirements.